Hubungan antara Attitude, Subjective Norms, serta Perceived Behavioural Control dengan Durasi "Binge-Watching" di Kalangan Mahasiswa - Akbar, M Aulia (Jurnal Studi Komunikasi, 2021)
The development in Video on Demand (VOD) services technology has proven to increase the chance of binge-watching. However, early literature about binge-watching only focuses on health risk and their opinion on this topic. Therefore, this study intended to find aspects that affect binge-watching duration among college students. Theory of planned behaviour (TPB) that discusses the role of attitude and intention on an individual’s behavior was applied to find the affected aspect of binge-watching duration. Variables such as need for completion, personalised suggestions, and cliffhanger were analysed as moderators. Participants of this study were active Indonesian undergraduate students who were selected by applying snowball sampling method. Data were collected using online questionnaire using Likert Scale and terbuka questions on Google Form. The results indicate that TPB, need for completion, personalised suggestions, and cliffhanger correlated to binge-watching duration among undergraduate students.